Optimizing Hanwoo steer performance and reducing environmental impact through dietary yeast hydrolysate - Purnamasari, Listya; dela Cruz, Joseph Flores; Hwang, Seong Gu (Jurnal Medik Veteriner, 2026)
Supplementation of ruminant diets with yeast hydrolysate (YH) can enhance feed efficiency and reduce manure gas emissions without causing adverse physiological effects. This study aimed to evaluate the effects of dietary supplementation with commercial YH on muscle growth, physiological responses, and fecal gas emissions in Hanwoo beef steers over a six-month feeding period. Thirty Hanwoo steers (7–8 months old; average body weight: 250 kg) were randomly allocated to three treatment groups (n = 10 per group; 5 steers per pen) and fed total mixed ration (TMR) diets supplemented with 0%, 0.1%, or 0.3% YH. Statistically, YH supplementation did not significantly affect growth performance parameters, including total weight gain, feed intake, average daily gain, and feed efficiency, nor did it alter blood characteristics or fecal noxious gas content. However, all measured values remained within normal physiological ranges, and steers receiving 0.1% YH showed numerically higher final body weight and weight gain compared to the other groups. Although not statistically significant, plasma insulin and dopamine concentrations tended to increase with YH supplementation. Notably, the concentrations of ammonia, hydrogen sulfide, and mercaptans in manure were significantly reduced (p < 0.05) in YH-supplemented groups relative to the control. These findings suggest that dietary inclusion of 0.1% YH may enhance growth performance, mitigate harmful gas emissions, and maintain the health status of Hanwoo steers.